Physiological Properties and Genome Structure of the Hyperthermophilic Filamentous Phage φOH3 Which Infects Thermus thermophilus HB8 - Nagayoshi, Yuko; Kumagae, Kenta; Mori, Kazuki; Tashiro, Kosuke; Nakamura, Ayano; Fujino, Yasuhiro; Hiromasa, Yasuaki; Iwamoto, Takeo; Kuhara, Satoru; Ohshima, Toshihisa; Doi, Katsumi (Frontiers in Microbiology, 2016)
A filamentous bacteriophage, φOH3, was isolated from hot spring sediment in Obama hot spring in Japan with the hyperthermophilic bacterium Thermus thermophilus HB8 as its host. Phage φOH3, which was classified into the Inoviridae family, consists of a flexible filamentous particle 830 nm long and 8 nm wide. φOH3 was stable at temperatures ranging from 70 to 90 °C and at pHs ranging from 6 to 9. A one-step growth curve of the phage showed a 60-min latent period beginning immediately postinfection, followed by intracellular virus particle production during the subsequent 40 min. The released virion number of φOH3 was 109. During the latent period, both single stranded DNA (ssDNA) and the replicative form (RF) of phage DNA were multiplied from min 40 onward. During the release period, the copy numbers of both ssDNA and RF DNA increased sharply. The size of the φOH3 genome is 5,688 bp, and 8 putative open reading frames (ORFs) were annotated. These ORFs were encoded on the plus strand of RF DNA and showed no significant homology with any known phage genes, except ORF 5, which showed 60% identity with the gene VIII product of the Thermus filamentous phage PH75. All the ORFs were similar to predicted genes annotated in the Thermus aquaticus Y51MC23 and Meiothermus timidus DSM 17022 genomes at the amino acid sequence level. This is the first report of the whole genome structure and DNA multiplication of a filamentous T. thermophilus phage within its host cell.